News and family affairs a content analysis of Manila Standard and Journal News Online's coverage of Marcos Jr.'s presidential campaign - Garcia, Beatriz Andrea H.
This research explored the editorial independence of Manila Standard and Journal News Online in view of the perceived familial and political conflict of interest between the Romualdez family and President Ferdinand Marcos Jr. Through a content analysis of online news articles and a series of in-depth interviews with journalists from both publications, this study showed that the majority of the news stories on the presidential campaign of Marcos Jr. were positively slanted towards him. Several factors including personal affiliation of reporters, background and nature of news outlet, self-imposed restraints at the reportorial level, failure to ensure objectivity in reporting, and failure to recognize ethical lapses were identified as possible reasons of the predominantly positive slant of the articles. Accounts of interview participants also showed that for Manila Standard, pushback from the editors allowed for a relatively balanced reportage, while bias was more evident in the newsroom processes of the Journal Group's newsrooms.